(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Iron oxide nanoparticles (IONPs) have emerged as versatile tools in modern pharmaceutical technology, significantly impacting drug delivery systems, diagnostics, and therapeutic interventions. These nanoparticles possess unique physicochemical properties, including high surface area, biocompatibility, and magnetic reactivity, making them ideal candidates for various biomedical applications. The incorporation of IONPs in pharmaceutical formulations has opened new avenues for precise drug delivery, imaging, and theranostics, addressing the limitations of traditional drug administration and diagnostics. Recent years have seen intensified research efforts focused on harnessing the capabilities of IONPs to enhance the efficacy, specificity, and safety of pharmaceutical interventions. The versatility of IONPs allows their use in combination therapies, as contrast agents for diagnostic imaging, and as carriers for targeted drug delivery to diseased sites. Additionally, their magnetic properties enable precise control over their movement within the body, facilitating targeted drug delivery and imaging with minimal side effects. This paper reviews the diverse applications of IONPs in modern pharmaceutical technology, emphasizing their role in advancing drug delivery systems and diagnostic techniques. By examining recent advancements and case studies, we aim to provide a comprehensive understanding of the potential benefits and challenges associated with the integration of IONPs in pharmaceutical research and development.